2020
DOI: 10.1039/d0ma00146e
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic optical properties of GeS investigated by optical absorption and photoreflectance

Abstract: We present a comprehensive study of bulk GeS optical properties and their anisotropy, by investigation of the fundamental band gap of the material and the energetically higher direct transitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 59 publications
5
38
0
Order By: Relevance
“…We found that the low-temperature (T = 5 K) optical band-gap absorption is governed by a single resonance related to the neutral exciton, while the corresponding emission is dominated by disorder/impurity-and/or phonon-assisted recombination processes. Moreover, both the RC and PL spectra are found to be linearly polarized along the armchair direction of the crystal, which is consistent with previous works [12,16,17]. The measured RS spectra as a function of temperature from 5 to 300 K are composed of six Raman peaks, the energies and symmetries of which are in agreement with phonon dispersion calculated using Density Functional Theory (DFT).…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…We found that the low-temperature (T = 5 K) optical band-gap absorption is governed by a single resonance related to the neutral exciton, while the corresponding emission is dominated by disorder/impurity-and/or phonon-assisted recombination processes. Moreover, both the RC and PL spectra are found to be linearly polarized along the armchair direction of the crystal, which is consistent with previous works [12,16,17]. The measured RS spectra as a function of temperature from 5 to 300 K are composed of six Raman peaks, the energies and symmetries of which are in agreement with phonon dispersion calculated using Density Functional Theory (DFT).…”
Section: Introductionsupporting
confidence: 90%
“…or absorption [17]. Moreover, according to the authors of [17], the X resonance can be related to the direct transition at the Γ point of the Brillouin zone (BZ), which is linearly polarized along the armchair crystallographic direction.…”
Section: Optical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is seen that both the emission and absorption signals of the X transitions are linearly polarized along the same direction (167 o and 170 o , respectively). The result confirms directly the same origin of the X feature apparent in both the PL and RC spectra, as previously reported independently for the emission 18 , photoreflectance 19 or absorption 20 . Moreover, according to Ref.…”
Section: B Optical Propertiessupporting
confidence: 91%